Aktivitas publik relation dalam meningkatkan citra Bank BSI di tengah dinamika pasar keuangan - Sholikhah, Laila Mar'atus (Maliki Interdisciplinary Journal, 2024)
This research discusses the role of Public Relations (PR) activities in improving the image of Bank Syariah Indonesia (BSI) in the midst of financial sector competition. Using a qualitative and case study approach, this research explores BSI's PR strategies, such as the use of social media, involvement in social activities, and Corporate Social Responsibility (CSR) programs. The findings showed that social media activities, such as education on sharia and financial products, as well as BSI's involvement in social activities, contributed positively to BSI's image. Communication transparency was also identified as an important factor in building customer trust. Overall, this research provides recommendations for BSI to continue developing effective PR strategies to maintain a positive image and increase competitiveness in the market.